Effectiveness of Maritime Sector Public Services: A Study of the Implementation of Immigration SOPs at the Tanjung Priok Port Terminal - Rahma Dyah Widyaningrum; Fedianty Augustinah; Eny Hartati (International Journal of Social Science and Humanity, 2025)
This study aims to explore the implementation of Standard Operating Procedures for immigration services at TPI Tanjung Priok Port and examine its impact on service effectiveness in Indonesia's maritime sector. The research employed a qualitative approach to analyse the gap between formal SOP guidelines and on-the-ground practices, examining internal and external factors, including resource limitations, technological constraints, and inter-agency coordination issues. The findings reveal significant disparities that lead to both positive and negative discretion amongst frontline Immigration officers, influencing service consistency, efficiency, and transparency. Negative discretion results in procedural deviations that compromise reliability and potentially foster corruption, delays, and inefficiencies. In contrast, positive discretion emerges as adaptive responses indicating weaknesses in SOP design or infrastructure. The study concludes that enhancing frontline officers' competence, motivation, and accountability is essential for achieving desired outcomes, whilst integrating technological solutions such as digital documentation and real-time monitoring is vital for streamlined, transparent, and accountable procedures. Improving SOP adherence, coupled with better resource allocation and inter-institutional cooperation, can significantly reduce vessel turnaround times, lower logistics costs, and bolster maritime competitiveness. The research advocates for dedicated training programmes, supervisory systems, and technological innovations to ensure SOP compliance, minimise discretion-driven deviations, and promote accountability, thereby optimising maritime service delivery and supporting Indonesia's strategic maritime development objectives.